Hubungan Dukungan Keluarga terhadap Kesiapan Wanita dalam Menghadapi Menopause - Erna Audina; Sri Wahyuni; Apriliani Yulianti Wuriningsih (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
Menopause was a phase of a woman’s life that occurred at the end of the menstrual cycle. In this phase, women needed to prepare physically and psychologically to face menopause. One of the factors that affected this preparation was family support. This study aimed to determine the relationship between family support and women’s readiness to face menopause. This study was a type of quantitative research with a cross-sectional research design. Sampling by purposive sampling technique with a sample of 77 respondents was statistically processed using the Gamma Test. The results of this study showed that there was a relationship between family support and women’s readiness to face menopause with P value < 0.05 and a correlation value of 1.000, which meant that the correlation between the two variables was very strong. There was a relationship between family support and women’s readiness to face menopause, a very strong correlation that meant that women with high support had readiness to face menopause, and women with low support did not have readiness to face menopause.